Increased probability of expression from modified retroviral vectors in embryonal stem cells and embryonal carcinoma cells. - Robbins, P B (1997)
Gene expression from the Moloney murine leukemia retrovirus (Mo-MuLV) is highly restricted in embryonic carcinoma (EC) and embryonic stem (ES) cells. We compared levels of expression in PA317 fibroblasts, F9 (EC) cells, and CCE (ES) cells by Mo-MuLV-based vectors and vectors based on our previously reported MND backbone, which has alterations to address three viral elements implicated as repressors of expression by Mo-MuLV: the enhancer, the primer binding site, and the negative-control region. Expression was evaluated with three reporter genes, the chloramphenicol acetyltransferase (CAT) gene, whose expression was measured by enzymatic assay and by Northern blotting; a truncated nerve growth factor receptor (tNGFR), whose expression was measured by fluorescence-activated cell sorting (FACS) as a cell surface protein; and the enhanced green fluorescent protein (EGFP), whose expression was measured intracellularly by flow cytometry. We found significantly higher levels of CAT activity (5- to 300-fold) and greater quantities of vector-specific transcripts in ES and EC cells transduced with the modified MND-CAT-SN vector than in those transduced with L-CAT-SN. Northern blot analysis indicated that long terminal repeat transcripts from MND-CAT-SN are >80 times more abundant than the L-CAT-SN transcripts. FACS analysis of tNGFR expression from a pair of vectors, L-tNGFR-SN and MND-tNGFR-SN, indicated that only 1.04% of the CCE cells containing the L-tNGFR-SN vector expressed the cell surface reporter, while the MND-tNGFR-SN vector drove expression in 99.54% of the CCE cells. Of the F9 cells containing the L-tNGFR-SN vector, 13.32% expressed tNGFR, while 99.89% of the F9 cells transduced with MND-tNGFR-SN showed expression. Essentially identical results were produced with an analogous pair of vectors encoding EGFP. In unselected pools of F9 cells 48 h posttransduction, the L-EGFP-SN vector drove expression in only 5% of the population while the MND-EGFP-SN vector drove expression in 88% of the cells. After more than 3 weeks in culture without selection, the proportion of cells showing expression from L-EGFP-SN decreased slightly to 3% while expression from the MND-EGFP-SN vector persisted in 80% of the cells. Interestingly, in the few ES and EC cells which did show expression from the L-tNGFR-SN or L-EGFP-SN vectors, the magnitude of reporter expression was similar to that from the MND-tNGFR-SN or MND-EGFP-SN vector in nearly all cells, suggesting that the MND vectors are far less susceptible to position-dependent variegation of expression than are the Mo-MuLV-based vectors. Therefore, the modified retroviral vector, MND, achieves higher net levels of expression due to a greater frequency of expression, which may be useful for the expression of exogenous genes in EC and ES cells.